Analysis of Availability of Input for Submission of National Health Insurance (NHI) Claims in Intensive Patients at Regional General Hospital Kendari City, Southeast Sulawesi Province - Alvionita Hanafi; Nani Yuniar; Suhadi, (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
National health insurance is organized by the Social Security Administration (SSA) which aims to raise funds for health. Hospitals as health service providers have the right to demand compensation for services provided to SSA Health. Claims management is the process for filing and paying claims for advanced healthcare. The claim rate approved by SSA can affect the hospital's income. During the implementation process, many hospitals experienced delays in the SSA claim submission process. The purpose of the study was to analyze the availability of input for submitting claims for national health insurance in inpatients at the Kendari City Regional General Hospital (RGH). The type of research used is qualitative research. Data was collected by means of in-depth interviews, observation and document review. Data analysis was performed using Content Analysis Matrix. The results showed that from the analysis using the Content Analysis Matrix between input nodes, it was found that the Standard Operating Procedure (SOP) variable got the highest number, followed by the Claim file variable. Based on this analysis, it can be seen that the SOP variables and claim files are one of the main causes of delays in the implementation of claim submissions at the Kendari City Hospital, followed by HR, rewards and Computerized Information Technology (ICT) variables as supporting variables for delays in NHI claims. Conclusion: The ratio of NHI claims officers is not proportional to the workload, There is no reward given by the hospital to health workers involved in the implementation of SSA claim submissions. There are still many medical record files that are often filled out incompletely by the Doctor in charge of patients and nurses, There is no SOP on the implementation of claim submissions in the case mix room and SOP for filling out medical records, ICT is still inadequate. Recommendation; the need for additional claims officers, training officers, giving rewards, fulfilling the availability of SOPs, and adding computerized information technology tools.